2021
DOI: 10.3390/ijms22084225
|View full text |Cite
|
Sign up to set email alerts
|

Bee Bread Ameliorates Vascular Inflammation and Impaired Vasorelaxation in Obesity-Induced Vascular Damage Rat Model: The Role of eNOS/NO/cGMP-Signaling Pathway

Abstract: Obesity and hyperlipidemia are major risk factors for developing vascular diseases. Bee bread (BB) has been reported to exhibit some biological actions, including anti-obesity and anti-hyperlipidemic. This study aims to investigate whether bee bread can ameliorate vascular inflammation and impaired vasorelaxation activity through eNOS/NO/cGMP pathway in obese rats. Forty male Sprague-Dawley rats were randomly divided into four groups (n = 10/group), namely: control (normal group), obese rats (OB group), obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Bee bread improved hyperlipidemia by lowering TG, TC and LDL levels, and, in contrast, increased the HDL level. Our results coincide with previous studies that reported the hypolipidemic effects of bee bread [ 41 , 42 , 76 ]. This beneficial property of bee bread could be ascribed to the presence of flavonoids, which have been reported to exert their antioxidative property towards LDL by inhibiting its susceptibility to oxidation [ 77 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bee bread improved hyperlipidemia by lowering TG, TC and LDL levels, and, in contrast, increased the HDL level. Our results coincide with previous studies that reported the hypolipidemic effects of bee bread [ 41 , 42 , 76 ]. This beneficial property of bee bread could be ascribed to the presence of flavonoids, which have been reported to exert their antioxidative property towards LDL by inhibiting its susceptibility to oxidation [ 77 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is confirmed by our present study in which significantly increased levels of pro-inflammatory mediators TNF-α and NF-κβ, and a significantly decreased level of anti-inflammatory cytokine IL-10 were observed in the liver of the HFD group, as well as elevation in serum lipids and the deposition of collagen fibers, which indicated the presence of liver fibrosis in this group. Bee bread (0.5 g/kg/day for 12 weeks) has been previously reported to suppress TNF-α and NF-κβ, and increase IL-10 levels in obesity-induced aortic vascular damage [ 76 ] and HFD-induced renal damage [ 43 ] rats. Our present findings are in agreement with previous reported studies, and further support the beneficial properties of bee bread against inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial changes in the aorta and increased IMT reflected atherosclerotic changes as postulated by previous study [ 55 ]. Moreover, Othman et al [ 56 ] clarified that thickening aortic wall and distorted elastic lamellae might be the factors that contributed to the impairment of the structural integrity of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Hemanth Kumar et al [ 35 ] attributed this to the formation of S-nitroso-Hcy following the exposure of endothelial cells to Hcy with a subsequent decrease in the bioactivity of NO. Furthermore, previous studies attributed the vascular dysfunction to the increased lipid concentration besides the initiation of inflammatory processes [ 56 , 60 ]. The reported accumulated blood cells and perivascular adipose tissue deposition indicated the presence of active inflammation as clarified by previous study [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first study conducted by Eleazu et al [ 30 ] revealed that the administration of bee bread in obese rats decreased the percentage change in body weight, BMI index, kidney weight, MDA concentrations, inflammatory cells in kidney tissue, NFkB, TNF-α, interleukin- l -beta, and Bax, while it increased the levels of SOD, GPx, GST, and TAA and reduced the Bowman’s capsule space in the urinary chambers of the kidneys. In the second study conducted by Othman et al [ 106 ], the administration of bee bread in obese male Sprague–Dawley rats improved their lipid profile, aortic inflammatory markers, and their impaired vasorelaxation activity, and showed its ability to enhance nitric oxide release and promote endothelial nitric oxide synthase (eNOS) and cyclic guanosine monophosphate (cGMP) immunoexpression. The same protocol forhigh-fat diet-induced obese rats was used by Suleiman et al [ 107 ] to examine the protective effect of bee bread at a dose of 0.5 g/kg once daily for 12 weeks on testicular oxidative stress, inflammation, apoptosis, and lactate transport in the testes of obese rats ( Table 4 ).…”
Section: The Pharmacological Effect Of Bee Bread: In Vivo Investigationsmentioning
confidence: 99%